COMPLEX REGIONAL PAIN SYNDROME (CRPS) DIAGNOSIS : A CASE REPORT - Shahdevi Nandar Kurniawan; Made Ayu Hariningsih Sunaga; Sri Budi Rianawati; Masruroh Rahayu (Journal of Pain, Headache and Vertigo, 2020)
Complex regional pain syndrome (CRPS) is a term that describes a variety of chronic pain conditions that are believed to result from dysfunction in the central or peripheral nervous systems. Epidemiological data from 2 major studies show a CRPS incidence between 5.5 and 26.2 cases per 100,000 people per year. A women, 35 years old came to the neurologic policlinic with complain ofÂ  persistent pain in half left body since a year ago. Pain characteristic was pains and needles sensation, sometimes numbness, tingling that spreaded from left neck until left fingers.we found vasomotor, sensoric and motoric disorder that appropriated with budapest criteria. To diagnose CRPS need to holistic examination and deeper anamnesa to prevent wrong diagnosis. Pain treatment in this patient was not easy. She already has undergone 7 times epidural block and taken medicines nevertheless quality of pain decreased in small number with VAS score 7-8.